Pengaruh Penggunaan Model Pembelajaran Terpadu (Integrited) Terhadap Prestasi Belajar Siswa di SMP Negeri 1 Jerowaru - M. Saipul Watoni (Pendidikan Al-Gafari, 2024)
Education is one activity that is universal in the life of humans, anywhere There is society, there is also education. Many countries recognize that problem education Is a complicated issue, however, everything feels that education is the State's very duty petting, a nation that wants to progress, build, and try to improve circumstances in society and the world, of course, the state that education is key, and without key business, they will fail. This research is a type of experiment that aims to determine the effect of using an integrated learning model on student learning achievement. Subject study This is student Class VIII of SMP Negeri 1 Jerowaru, totaling 68, were selected sample. Class experiment 35 people and classes control 33 people. Data collection techniques use observation and tests. Data analysis techniques use normality tests, homogeneity tests, and hypothesis tests using the t-test formula. The research results obtained an average value for the class experiment = 61.37. Whereas For class control average value = 43.12, there is a difference or difference in average value between class experiments and classes control equal to = 18.25 and results from hypothesis testing using t-test formula = 4.62 of results study can conclude that the learning model integrated (integrated) effective to performance Study student.